Histoplasma and Histoplasmosis - Bongomin, Felix (IntechOpen, 2020)
Histoplasma and Histoplasmosis is a book on epidemiology, diagnosis, and treatment of histoplasmosis. It is an all-inclusive source of knowledge for both specialist and non-specialist mycologists at various levels of training or work experience.Through collaborative efforts of the authors and the editor, this book provides up-to-date information on the global distribution of histoplasmosis, an updated estimation of the burden of histoplasmosis in Asia, and recent advances in laboratory diagnosis and treatment of histoplasma and histoplasmosis. This volume is an invaluable source of knowledge for trainees and practitioners alike.